2014
DOI: 10.1097/cji.0000000000000043
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Primary Acute Myeloid Leukemia Identifies Biomarkers Predicting Susceptibility to Human Allogeneic Vγ9Vδ2 T Cells

Abstract: Allogeneic innate lymphocytes such as Vγ9Vδ2 T cells are attractive candidates for cancer immunotherapy as they provide MHC-unrestricted antitumor activity without clinical evidence for inducing graft-versus-host disease (GvHD). However, current cellular immunotherapy approaches lack predictive biomarkers identifying patient cohorts most susceptible to immune attack. For this purpose we performed a comprehensive analysis of clinical, genetic, metabolic, and immunophenotypic features of 19 primary acute myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…16 These monocytic Low AML were shown to have poorly active mevalonate pathway. 16 This could account for a poor pAg accumulation in these blasts upon N-BP treatment that would fail to activate Vg9Vd2 T cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 These monocytic Low AML were shown to have poorly active mevalonate pathway. 16 This could account for a poor pAg accumulation in these blasts upon N-BP treatment that would fail to activate Vg9Vd2 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…16 These monocytic Low AML were shown to have poorly active mevalonate pathway. 16 This could account for a poor pAg accumulation in these blasts upon N-BP treatment that would fail to activate Vg9Vd2 T cells. 29 We show that anti-BTN3A 20.1 mAb can sensitize N-BP-poorly sensitized primary AML blasts to Vg9Vd2T cells lysis, notably monocytic Low AML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that post-remission therapy is essential for AML patients with complete hematologically-defined remission. (5). It has also been reported that increased consumption of fruits and vegetables can decrease the risk of cancer (6), cardiovascular disease and atherosclerosis in humans (7).…”
Section: Introductionmentioning
confidence: 99%